UJI AKTIVITAS TOKSISITAS DARI EKSTRAK METANOL DAN ETIL ASETAT TOTAL DAUN BAWANG BATAK (Allium chinense G. Don) - Aliyah Fahmi (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2020)
This research aims to determine toxicity activity test of methanol and ethyl acetate total from Batak leeks (Allium chinense G. Don). The method was using the Brine Shrimph Letality Test (BSLT). Methanol and ethyl acetate extracts of Batak leeks were diluted using salt solution with concentration variations (10, 100, 1000)ppm. Salt solution also was used as negative blank. The research model was in Vitro experimental research model. The results showed that methanol extract of Batak leeks on 6576578 mg / L which was non-toxic and LC50 on ethyl acetate extract of Batak leeks was 16.59 mg / L which was a strong toxic compound.